The Impact of Social Commerce On Local Sme Resilience In Indonesia: Evaluating The Effectiveness Of The Tiktok Shop Prohibition Policy - Arina Manasikana; Sri Purnama Sari; Eka Nurmala; Zizi Arsyabila (Journal of Economics Business Industry, 2024)
The Indonesian government enacted Ministerial Regulation on Trade (Permendag) No. 31 of 2023, which took effect on October 4, 2023, prohibiting social commerce platforms from conducting direct retail transactions. This regulation was primarily directed at TikTok Shop, which had amassed approximately 2.1 million registered sellers in Indonesia by mid-2023. The central policy rationale was that unfettered social commerce activity was eroding the revenue base of traditional and physical market-based SMEs. This study evaluates the actual effectiveness of this prohibition from the perspective of local SME resilience, examining whether the regulation genuinely enhanced market access and revenue recovery for physical marketplace sellers, or whether it created new barriers to digital market participation for SMEs that had invested in online channels. A mixed methods design was employed, combining a structured survey of 245 SMEs across Greater Jakarta (Jabodetabek) with in-depth interviews of 18 key informants from market associations, SME cooperatives, and government trade officials. Data collection took place between October 2023 and January 2024. Quantitative analysis used ordinary least squares regression and difference-in-differences estimation, while qualitative data were analyzed thematically. Findings reveal a highly asymmetric impact: physical-market SMEs experienced a statistically significant average revenue increase of 18.3 percent in the two months following the ban, while digitally dependent SMEs reported an average revenue contraction of 43.6 percent over the same period. The regulation effectively displaced the problem rather than resolving its structural cause. Policy recommendations emphasize a hybrid regulatory framework that separates predatory pricing enforcement from platform access restrictions, enabling equitable market participation across both physical and digital channels.